2021
DOI: 10.3389/fmolb.2021.700078
|View full text |Cite
|
Sign up to set email alerts
|

miR-10a-5p Inhibits the Differentiation of Goat Intramuscular Preadipocytes by Targeting KLF8 in Goats

Abstract: Intramuscular fat contributes to the improvement of meat quality of goats. MicroRNAs (miRNAs) have been reported to regulate adipocyte differentiation and maturation. The aim of our study was to clarify whether miR-10a-5p regulates goat intramuscular preadipocyte (GIPC) differentiation and its direct downstream signaling pathway. GIPCs were isolated from longissimus dorsi, whose miR-10a-5p level was measured at different time point of differentiation induction. Adipogenic differentiation of the GIPCs was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…The same result was observed in the rescue experiment of this study. Also, the same problem has been found in previous studies ( Guo et al, 2020 ; Xu et al, 2021 ; Chen et al, 2022 ). In addition, pref-1 , a well-known negative regulator of adipogenesis, was positively correlated with miR130b duplex (miR-130b-3p and miR-130b-5p) and KLF3 regulated goat intramuscular adipocyte differentiation.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The same result was observed in the rescue experiment of this study. Also, the same problem has been found in previous studies ( Guo et al, 2020 ; Xu et al, 2021 ; Chen et al, 2022 ). In addition, pref-1 , a well-known negative regulator of adipogenesis, was positively correlated with miR130b duplex (miR-130b-3p and miR-130b-5p) and KLF3 regulated goat intramuscular adipocyte differentiation.…”
Section: Discussionsupporting
confidence: 86%
“…The medium was changed 24 h later. The preadipocytes were then identified by Oil red O staining at different time points (3, 24, 48, 72, 96, and 120 h) with differentiation induction ( Xu et al, 2021 ). With the extension of differentiation induction, lipid droplets became larger and accumulation increased.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, miR-10a-5p enhanced adipogenic differentiation in porcine precursor adipocytes. However, within goat intramuscular preadipocytes, it inhibited differentiation by targeting KLF8 [38]. This discrepancy might be due to interspecies differences.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have shown that ncRNAs, including microRNAs (miRNAs), long non-coding RNAs (lncRNAs) and circRNAs, are capable of participating in the process of lipid metabolism, including the proliferation and differentiation of adipocytes, the formation of fat droplets, and the activation of adipocyte-specific genes, as well as the regulation of genes during the development and remodeling of adipose tissue [ 8 , 9 , 10 ]. In goats, miR-10a-5p targets Krüppel-like factor 8 ( KLF8 ) and inhibits differentiation of intramuscular preadipocytes [ 11 ]. Through attenuation of phosphorylation of mitogen-activated protein kinase (MAPK)-p38 and MAPK-extracellular signal-regulated kinase 1/2 (ERK1/2), lnc-FR332443 positively regulates Runx1 expression and suppresses adipocyte differentiation in mouse adipocytes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%